Silicon Nitride Deposition for Flexible Organic Electronic Devices by VHF (162 MHz)-PECVD Using a Multi-Tile Push-Pull Plasma Source. Issue 1 (December 2017) - Kim, Ki; Kim, Ki; Ji, You; Park, Jin; Shin, Jae; Ellingboe, Albert; Yeom, Geun
Abstract Depositing a barrier film for moisture protection without damage at a low temperature is one of the most important steps for organic-based electronic devices. In this study, the authors investigated depositing thin, high-quality SiNx film on organic-based electronic devices, specifically, very high-frequency (162 MHz) plasma-enhanced chemical vapor deposition (VHF-PECVD) using a multi-tile push-pull plasma source with a gas mixture of NH3 /SiH4 at a low temperature of 80 °C. The thin deposited SiNx film exhibited excellent properties in the stoichiometry, chemical bonding, stress, and step coverage. Thin film quality and plasma damage were investigated by the water vapor transmission rate (WVTR) and by electrical characteristics of organic light-emitting diode (OLED) devices deposited with SiNx, respectively. The thin deposited SiNx film exhibited a low WVTR of 4.39 × 10−4 g (m2 · day)−1 for a single thin (430 nm thick) film SiNx and the electrical characteristics of OLED devices before and after the thin SiNx film deposition on the devices did not change, which indicated no electrical damage during the deposition of SiNx on the OLED device.